2019
DOI: 10.1002/btpr.2828
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the methods used for finding surface energy to investigate protein interaction behavior on chromatographic supports

Abstract: Hydrophobic interaction chromatography, an important and effective purification strategy, is generally used for the purification of variety of biomolecules. A basic understanding of the protein interaction behavior is required to effectively separate these biomolecules. A colloidal type extended Derjaguin, Landau, Verwey, and Overbeek calculations were utilized to study the interactions behavior of model proteins to commercially available hydrophobic chromatographic materials that is, Toyopearl Phenyl 650C and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…A recent study has also been published on the comparison of different surface energy determination methods. An interconversion factor was proposed to convert the secondary energy minimum obtained through SDM and CPM 20 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study has also been published on the comparison of different surface energy determination methods. An interconversion factor was proposed to convert the secondary energy minimum obtained through SDM and CPM 20 …”
Section: Resultsmentioning
confidence: 99%
“…Adsorption of colloidal particles (proteins, biomass) depends on the surface properties of both biological molecules and chromatographic materials 23,24 . Different components of surface energy can be calculated from the experimentally determined contact angle (for the determination of Lifshitz van der Waals and acid base components of surface energy) and zeta potential values (for the determination of electrostatic component of surface energy) 2,20,25 . Various studies reported that the adsorption of biomolecules onto ion exchange chromatographic materials is mainly influenced by the zeta potential of the biomolecules and adsorbents 26,27 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations